2023
DOI: 10.1186/s12951-023-02148-y
|View full text |Cite
|
Sign up to set email alerts
|

Nano-selenium enhances melon resistance to Podosphaera xanthii by enhancing the antioxidant capacity and promoting alterations in the polyamine, phenylpropanoid and hormone signaling pathways

Lu Kang,
Yangliu Wu,
Yujiao Jia
et al.

Abstract: Powdery mildew is one of the main problematic diseases in melon production, requiring the use of chemical pesticides with disease-resistant cultivars for control. However, the often rapid acquisition of fungicidal resistance by mildew pathogens makes this practice unsustainable. The identification of crop treatments that can enhance resistance to powdery mildew resistance is therefore important to reduce melon crop attrition. This study indicates that the application of Nano-Se can reduce the powdery mildew di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 73 publications
0
7
0
Order By: Relevance
“…Numerous studies have shown that nanomaterials can significantly promote plant growth ( Arora et al, 2012 ; Nair, 2016 ), and its mechanism of action is multifaceted, including enhancing photosynthesis ( Liu et al, 2023 ; Mehmood et al, 2023 ), improving the leaf or rhizosphere microbial communities ( Karnwal et al, 2023 ; Liu et al, 2023 ), alleviating oxidative stress and enhancing antioxidant enzyme activity ( Wu et al, 2023 ), and increasing the availability of nutrients in plants ( Ahmed et al, 2022 ), regulating plant hormones and metabolism ( Kang et al, 2023 ), and so on. The results of this study was consistent with part of previous studies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Numerous studies have shown that nanomaterials can significantly promote plant growth ( Arora et al, 2012 ; Nair, 2016 ), and its mechanism of action is multifaceted, including enhancing photosynthesis ( Liu et al, 2023 ; Mehmood et al, 2023 ), improving the leaf or rhizosphere microbial communities ( Karnwal et al, 2023 ; Liu et al, 2023 ), alleviating oxidative stress and enhancing antioxidant enzyme activity ( Wu et al, 2023 ), and increasing the availability of nutrients in plants ( Ahmed et al, 2022 ), regulating plant hormones and metabolism ( Kang et al, 2023 ), and so on. The results of this study was consistent with part of previous studies.…”
Section: Discussionmentioning
confidence: 99%
“… Ahmed et al (2022) demonstrated that chitosan-iron nanocomposite controlled bacterial leaf blight by regulating the defense response and nutritional status of rice plants. Kang et al (2023) proved that nano-selenium enhances melon resistance to Podosphaera xanthii by enhancing the antioxidant capacity and promoting hormone signaling pathways. This study found that MgO NPs treatment significantly increased SA content in the root of tumorous stem mustard, and also significantly increased the antioxidant enzyme activity ( Figure 3 ), which was similar to the results of those studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Under biotic stress that resulted from Xanthomonas albilineans infection, nano-Se supported the growth of sugarcane as an eco-fungicide and improved the juice quality [202]. The suggested mechanism of nano-Se for plant disease resistance involves enhancing the capacity of antioxidants, inducing the pathway of jasmonic acid, reducing the accumulation of ROS and H 2 O 2 , and promoting the pathways for phytohormones signaling [171,202,210]. Many studies have confirmed the role of nano-Se in inducing the resistance of crops to phytopathogens such as Botrytis cinerea in cucumber [211], spot blotch disease in wheat [212], Podosphaera xanthii in melon [210], Fusarium-induced wilt disease in lettuce [209], and Alternaria leaf spot disease in the common bean [53].…”
Section: Seedling Productionmentioning
confidence: 99%
“…The suggested mechanism of nano-Se for plant disease resistance involves enhancing the capacity of antioxidants, inducing the pathway of jasmonic acid, reducing the accumulation of ROS and H 2 O 2 , and promoting the pathways for phytohormones signaling [171,202,210]. Many studies have confirmed the role of nano-Se in inducing the resistance of crops to phytopathogens such as Botrytis cinerea in cucumber [211], spot blotch disease in wheat [212], Podosphaera xanthii in melon [210], Fusarium-induced wilt disease in lettuce [209], and Alternaria leaf spot disease in the common bean [53]. Along with the mitigation of stress, other benefits that have been reported due to nano-Se in farming include nano-biofortification [204,205], improving the quality and shelf life of harvested crops [213], and mitigation of abiotic stresses, including salinity [214], heavy metals [215], and drought [216].…”
Section: Seedling Productionmentioning
confidence: 99%